Change in Care Dependency of Stroke Patients: A Longitudinal and Multicenter Study - Nursiswati Nursiswati, MN; Ruud J.G. Halfens, PhD; Christa Lohrmann, PhD, MA, RN (Elsevier, 2017)
Purpose: The study was conducted to investigate the change of care dependency in stroke patients from inpatient wards and outpatient units in Indonesia. Methods: This study is longitudinal and multicentered. One hundred and nine patients were included from four hospitals on the island of Java. Care dependency was assessed using the Indonesian version of the 15-item Care Dependency Scale (CDS) at five points in time: at inpatient wards for admission and discharge and at outpatient units after discharge in the 1st week, the 5th week, and the 13th week. Results: Most of the patients were male (65.1%), and diagnosed with ischemic stroke (71.5%). The results showed that care dependency in stroke patients decreased significantly from admission to discharge, as well as from the 5th to the 13th week as measured by the CDS. At admission, 23.0% of the patients were completely dependent on care, and at the 13th week about 1.0% were. Patients' care dependency decreased significantly in all care dependency items of the CDS in the inpatient ward, but five care dependency items of the CDS did not significantly decrease in the outpatient unit. Conclusions: Based on the findings of this study, we recommend that hospital-based and community-based services should include continual care dependence monitoring using this comprehensive instrument. Care dependency is subject to change over time, therefore nurses have to plan and tailor adequate nursing care measures to patient needs in the different stages, especially with respect to the aspect of mobility.